1984
DOI: 10.1007/bf02405292
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopic study of calcium phosphate formation in supersaturated solutions seeded with apatite

Abstract: The present study examined crystal growth on enamel and synthetic apatite seed surfaces in dilute supersaturated solutions by means of transmission electron microscopy. At all supersaturations, new growth initially appeared on the ends of the seed crystal. In solutions undersaturated with respect to octacalcium phosphate (OCP), this growth was needlelike in appearance. Above the solubility point for OCP, the growth frequently took the form of thin, platelike crystals. The relevance of these findings to precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Thus, remineralization of a partially-demineralized collagen matrix is thermodynamically more favorable than homogeneous nucleation within a completely-demineralized collagen matrix. Part of the success reported with the use of contemporary calcium- and phosphate-releasing remineralizing materials may be related to the remineralization of the collagen matrix via epitaxial growth of calcium phosphate salts on remnant seed crystallites [23]. Epitaxial growth may be regarded as a top-down approach according to the classical crystallization theory, via ion-by-ion addition to pre-existing seed crystallites [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, remineralization of a partially-demineralized collagen matrix is thermodynamically more favorable than homogeneous nucleation within a completely-demineralized collagen matrix. Part of the success reported with the use of contemporary calcium- and phosphate-releasing remineralizing materials may be related to the remineralization of the collagen matrix via epitaxial growth of calcium phosphate salts on remnant seed crystallites [23]. Epitaxial growth may be regarded as a top-down approach according to the classical crystallization theory, via ion-by-ion addition to pre-existing seed crystallites [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter study, we suppose that Ca/P of 1.34 indicated that the HOS cells would formed OCP. Ca binding sites and Ca receptors are likely to be involved initial process of OCP formation in vivo (Chattopadhyay N et al, 1996;Nancollas GH et al, 1974;Doi Y et al, 1984). There is a possibility of epitaxial relationship of HA, and HA is present epitaxially on the OCP surface whereas OCP is a precursor to HA (Brown WE et al, 1962, 1966, 1987Cheng PT, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…5 and 10) . It has been demonstrated that the morphology of the deposited apatite changes depending on the degree of solution supersaturation 31) . According to this finding, deposition of the plate-like crystals formed on the heated titanium substrate seemed to be due to a high degree of solution supersaturation achieved by increasing the temperature of the metastable solution in contact with the substrate.…”
Section: Morphology Of the Deposited Ha Crystalsmentioning
confidence: 99%